PREDICTION OF SOIL WATER CHARACTERISTIC CURVE USING PHYSICALLY BASED SCALING TECHNIQUE - S. Y. Liu; N. Yasufuku; Q. Liu; J. Yu (Lowland Technology International, 2013)
The soil water characteristic curve (SWCC) is an important hydraulic parameter for modeling water flow and contaminant transport in the vadose zone. However, direct measurement of the SWCC is still difficult. The Arya and Paris (AP) model estimates the SWCC from particle-size distribution curve (PSD) based on the shape similarity of the two curves. They introduced an empirical parameter, a, used to scale pore attributes from hypothetical formations to natural structure. Several approaches have been used to derive a. However, the calculation precedures of these approaches are either quite complicated or are developed without paying much attention to the physical significance of the soil properties. In the present paper the physically based scaling technique (PBS) was applied to derive a for the AP model. Fifty soil samples, representing a range of textures that include sand, sandy loam, loam, sit loam, and clay, were selected from UNSODA hydraulic property database for calculating a using PBS approach. In addition, nineteen soil samples with different textures were used to verify effectiveness of proposed a values. The result compared with other approaches show that the PBS technique combine with the AP model is a more useful and easier approach to predict SWCC from PSD.